PRODUKTVITAS PENJUALAN FURNITURE GLASS DI MASA PANDEMI COVID-19 (Studi Margo Glass Gallery Sukoharjo) - Haq, Adam Munirul; Aristin, Checilia Ayuningtias Putri; Aji, Nagasa Waka; Safitri, Rieke Alisyiya Nur; Santosa, Aris Prio Agus; Suyatno, Agus (Review of Accounting and Business, 2021)
Glass Furniture Industry is one of the growing industrial sectors in Indonesia. Providing attractive interior design and artistic value so as to bring comfort to consumers and make it their own value for art connoisseurs. Furniture not only has the function of comfort and neatness but also carries social meanings. Furniture indirectly conveys a person's economic status. This study aims to determine the impact and sales turnover on Margo Glass Gallary during the COVID-19 pandemic. This research method uses a case study approach with primary collection obtained by Margo Glass Gallery Sukoharjo through interviews. The results obtained are analyzed qualitatively. The results showed that sales and orders for furniture glass products at Margo glass Gallery decreased by 60% during the pandemic due to delays in the distribution process, due to restrictions on activities, both shipping from within the country and abroad, especially shipments abroad which were constrained in shipping. custody of goods.